The Role of Online Videos in Undergraduate Casual-Leisure Information Behaviors (Global Journal of Human-Social Science, 2016)
This study describes undergraduate casual-leisure information behaviors relevant to online videos. Diaries and in-depth interviews were used to collect data. Twenty-four undergraduates participated in this study (9 men, 15 women; all were aged 18-22 years). This study proposes a model of casual-leisure information behaviors and contributes new insights into user experience in casual-leisure settings, such as online video programs, with implications for other information domains.
Keywords: casual-leisure information behaviors; information behavior; online videos; role